The edge [large type] - Baldacci, David (Baldacci, David. 6:20 man, 2023)
When CIA operative Jenny Sikwell is murdered in rural Maine, government officials have immediate concerns over national security. Her laptop and phone were full of state secrets that, in the wrong hands, endanger the lives of countless operatives. In need of someone who can solve the murder quickly and retrieve the missing information, the U.S. government knows just the chameleon they can call on. Ex-Army Ranger Travis Devine spent his time in the military preparing to take on any scenario, followed by his short-lived business career chasing shadows in the deepest halls of power, so his analytical mind makes him particularly well-suited for complex, high-stakes tasks. Taking down the world s largest financial conspiracy proved his value, and in comparison, this case looks straightforward. Except small towns hold secrets and Devine finds himself an outsider again. Devine must ingratiate himself with locals who have trusted each other their whole lives, and who distrust outsiders just as much. Dak, Jenny s brother, who s working to revitalize the town. Earl, the retired lobsterman who found Jenny s body. And Alex, Jenny s sister with a dark past of her own. As Devine gets to know the residents of Potter, Maine, answers seem to appear and then transform into more questions. There s a long history of secrets and those who will stop at nothing to keep them from being exposed. Leaving Devine with no idea who he can trust... and who wants him dead.